ANALISIS PENGGUNAAN GAYA BAHASA GURU PENDIDIKAN USIA DINI DALAM PROSES PEMBELAJARAN - Anggi, Handani (IKIP Siliwangi, 2020)
This research describes the teacher's language style in the learning process, this study uses descriptive qualitative research to examine the language style used during the process of teaching and learning activities directly. The title raised in this study is